Characterization of a Multiseeded (msd1) Mutant of Sorghum for Increasing Grain Yield. Issue 5 (1st September 2014) - Burow, Gloria; Xin, Zhanguo; Hayes, Chad; Burke, John
ABSTRACT: Sorghum [ Sorghum bicolor (L.) Moench] has branched panicles with primary, secondary, and tertiary branches. These inflorescence branches are composed of a terminal triplet spikelet, consisting of one sessile (directly attached to the branch) and two pedicellate (spikelets attached to the branch through a short pedicel), followed by one or more spikelet pairs (one sessile and one pedicellate). In BTx623, and most sorghum lines, only the sessile spikelets can develop into seeds and the pedicellate spikelets, occasionally developing anthers, eventually abort. Here, we report the isolation and characterization of a stable multiseeded ( msd1 ) mutant of sorghum (in BTx623 background, referred to as wild‐type [WT]) in which both sessile and pedicellate spikelets are fertile. In addition, this mutant displayed increased length and total number of primary and secondary inflorescence branches. Genetic analysis showed that this multiseeded mutation is a recessive trait. Pedicellate spikelets in msd1 mutants exhibited complete flower with functional ovary and anthers, of which 75 to 95% can develop into viable seeds. The individual msd1 seeds are smaller than WT; however, the results indicated that this reduction in seed weight can be compensated by the increase in seed number. The total seed weight per panicle in msd1 mutants was increased by 30 to 40% as compared to the WT. Further experiments are needed to demonstrate whether the msd1 mutation can increase grain yield under field conditions.